2021
DOI: 10.1177/1055665620984643
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Severity of Craniosynostosis: Implications for Speech and Neurodevelopment

Abstract: Background: Single-suture craniosynostosis (SSC) can be associated with neurodevelopmental deficits. We examined the correlation between morphologic severity and incidence of speech-language or psychological concerns. Methods: In 62 patients (33 sagittal, 17 metopic, and 12 unicoronal), morphologic severity was determined via preoperative computed tomography (CT). Severity metrics for sagittal, metopic, and unicoronal synostosis were adjusted cephalic index (aCI), interfrontal angle (IFA), and anterior cranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Gabrick et al found out that neurologic symptoms are related to the degree of narrowing of the frontal skull, 34 and some studies 43,44,67,68 demonstrated significant developmental and psychological improvements occur after decompressive cranioplasty. On the other hand, other studies 31,69 found no correlation between the degree of morphologic severity and incidence of speech-language or psychological concerns for patients with metopic synostosis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Gabrick et al found out that neurologic symptoms are related to the degree of narrowing of the frontal skull, 34 and some studies 43,44,67,68 demonstrated significant developmental and psychological improvements occur after decompressive cranioplasty. On the other hand, other studies 31,69 found no correlation between the degree of morphologic severity and incidence of speech-language or psychological concerns for patients with metopic synostosis.…”
Section: Discussionmentioning
confidence: 89%
“…The most frequently used craniometric parameters (Supplementary Digital Content, Table 2, http://links.lww.com/SCS/D285) were: the interfrontal angle (IFA, Fig. 3D, used in 12 studies 11,17,19,21,[25][26][27][28][29][30][31][32] ), the endocranial bifrontal angle (ECA or EBA or EBF, Fig. 3E, used in 9 studies 12,23,24,[33][34][35][36][37][38] ), the interfrontal divergence angle (IFDA, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Tandon et al found that in patients with unilateral coronal synostosis, preoperative morphological severity is significantly associated with speech-language concerns, but not psychological concerns, at school age. 33 Research has not yet considered whether postoperative severity is also associated with these speech outcomes. Notably, other studies that investigated cognitive and psychosocial outcomes in craniosynostosis 16 used more intensive assessment batteries than the measures used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Abnormalities of speech and language have been reported among patients with SCS 11,12 and NSCS. [13][14][15][16][17] These abnormalities include language acquisition delay/disorder, speech production delay/disorder, hypernasality, and velopharyngeal insufficiency. 14,18 Moreover, hearing loss has been noted in both SCS and NSCS, which substantially impairs language acquisition and development.…”
Section: Introductionmentioning
confidence: 99%